(untitled) (Socio-economic relations in the digital society, 2019)
The processes of capitalization of the banking system, the state and the problem of capitalization of the banking sector in Ukraine, the basic legislative changes and their impact on the level of capitalization of banks in Ukraine in terms of economic instability. It was found that the change of certain provisions of the complex temporary anti-crisis measures will contribute to the recapitalization of banks, restructuring of external loans and ensure transparent application of the rules on the prohibition on early repayment of residents external borrowings. However, the equity capitalproblem most acute for the commercial banks with the Ukrainian owners. It is necessary to implement mechanisms of economic growth, stable positive balance of payments, strengthen the protection of the rights of both lenders and borrowers, and gain confi dence and fi nancial literacy of potential consumers of banking services.